2007
DOI: 10.1089/lap.2006.0243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Metoclopramide, Ondansetron, and Granisetron on the Prevention of Nausea and Vomiting After Laparoscopic Cholecystectomy

Abstract: Granisetron, when given prophylactically, resulted in a significantly lower incidence of PONV than metoclopramide and ondansetron, whereas metoclopramide was ineffective. Garnisetron may be an effective treatment in the proflaxy of PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…No statistically significant effects were observed (OR 1.92, 95 % CI 0.30–12.21). Twenty-five studies were excluded from this analysis because they reported zero events in both arms [38, 41, 44, 55, 56, 58, 62, 67, 70, 72, 77, 78, 80, 107, 109, 115, 120, 126, 128, 130, 131, 134, 149, 157, 158]. …”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant effects were observed (OR 1.92, 95 % CI 0.30–12.21). Twenty-five studies were excluded from this analysis because they reported zero events in both arms [38, 41, 44, 55, 56, 58, 62, 67, 70, 72, 77, 78, 80, 107, 109, 115, 120, 126, 128, 130, 131, 134, 149, 157, 158]. …”
Section: Resultsmentioning
confidence: 99%
“…22 Another study suggested that granisetron is more effective than inhalation isopropyl alcohol in preventing postoperative nausea and vomiting ( PONV ) following laparoscopic procedures, yet no significant difference was found between granisetron prophylaxis and no prophylaxis at all. 23 Other studies have shown granisetron to be more effective than other drugs in preventing PONV post laparoscopy, 24 especially when combined with steroid agents. 25,26 Subjects received doses ranging from 35.3 mg/kg to 77.5 mg/kg, and only when given in doses greater than 45 mg/kg was the drug more effective than the placebo, with its efficacy increasing proportionately with dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, anti-cholinergics, anti-histamines and phenothiazines were used to prevent PONV (8); but low effect of these medications and their complications led to drug shifts. Recent studies have shown that serotonin receptor antagonists are more effective than previous medications in PONV prophylaxis (3,9). It has been proved that Granisetron and Ondansetron are effective medications in this field (9) but by considering the high price of these drugs, suitable substitutes are required.…”
Section: Introductionmentioning
confidence: 99%